Centromeres cluster de novo at the beginning of meiosis in Brachypodium distachyon. - Ruoyu Wen; Graham Moore; Peter J Shaw (PLoS ONE)
In most eukaryotes that have been studied, the telomeres cluster into a bouquet early in meiosis, and in wheat and its relatives and in Arabidopsis the centromeres pair at the same time. In Arabidopsis, the telomeres do not cluster as a typical telomere bouquet on the nuclear membrane but are associated with the nucleolus both somatically and at the onset of meiosis. We therefore assessed whether Brachypodium distachyon, a monocot species related to cereals and whose genome is approximately twice the size of Arabidopsis thaliana, also exhibited an atypical telomere bouquet and centromere pairing. In order to investigate the occurrence of a bouquet and centromere pairing in B distachyon, we first had to establish protocols for studying meiosis in this species. This enabled us to visualize chromosome behaviour in meiocytes derived from young B distachyon spikelets in three-dimensions by fluorescent in situ hybridization (FISH), and accurately to stage meiosis based on chromatin morphology in relation to spikelet size and the timing of sample collection. Surprisingly, this study revealed that the centromeres clustered as a single site at the same time as the telomeres also formed a bouquet or single cluster.